Berani Bermimpi Menjadi Wirausaha Di Usia Muda - Slahanti, Masine; Sulistyowati, Rini Indah; Setiadi, Sofyandanu (Sejahtera: Jurnal Inspirasi Mengabdi Untuk Negeri, 2023)
Entrepreneurship is no longer something foreign to understand and even do, especially in the current era of globalization and digitalization. Many people understand entrepreneurship and there are even people who have become successful entrepreneurs, but how to become an entrepreneur, how to start or what to do is still unclear. Many people don't understand it, and the same goes for today's young people, there are still some who don't understand how to start becoming an entrepreneur. Even though there are also many young people in other big cities who have successfully owned several businesses. OnThis opportunity for Community Service wants to provide insight into understanding how to start becoming an entrepreneur at a young age by exploring the potential that exists in each person or by looking at the surrounding environment, hobbies and so on. So as to provide motivation for young people, especially those who join in King Generation Indonesian Bethel Church Jomblang Semarang Branch. The activity will be held by holding a seminar with presentations and opportunities for questions and answers. The hope is that with this activity, young people will be motivated to explore their potential and develop what they have to become young entrepreneurs